Towards a new generation of functional fiber-based packaging: cellulose nanofibers for improved barrier, mechanical and surface properties - Tarrés, Quim (2017)
The present work shows the suitability of using industrial fluting papers as raw material for the development of four different substrates, enzymatically refined and/or containing cellulose nanofibers (CNF) in bulk. These four substrates were deeply studied and treated with different coating formulations, containing cellulose nanofibers, polyvinyl alcohol, native starch and alkyl ketene dimer, with the purpose of evaluating the benefits of using fiber-based packaging paper with improved mechanical, physical and barrier properties. The results showed that tensile properties of paper can be significantly improved if CNF are coated in combination with PVA, at the same time that grease resistance was improved, air permeability and water vapor transmission rate were decreased. The obtained papers presented interesting barrier properties to vapor and air, at the same time that unconceivable limits of breaking length were achieved (6.44 km). In addition, when a second layer of alkyl ketene dimer was coated on both sides of paper, water contact angle was significantly improved, being higher than 115°, although the rest of the properties were slightly worsened. Overall, the present work shows the feasibility of using recycled fibers for the production of high value-added papers that could be used for packaging purposes due to their improved barrier and mechanical properties, promoting bio-based economy and circularity of the resources